The association between MRI texture analysis and chemoradiotherapy outcomes in glioblastoma cases (Annals of Medical Research, 2021)
Aim: Texture analysis can provide additional information regarding tumor heterogeneity and treatment response. The aim of this study was to evaluate whether MRI texture analysis can predict radiotherapy response and survival in glioblastoma patients.Material and Methods: A total of 26 patients with pathologically confirmed glioblastoma who had received curative chemoradiotherapy (60 Gy radiotherapy + temozolomide) underwent contrast-enhanced cranial MRI texture analysis before and after chemoradiotherapy. The region of interest was determined as the active tumor area in post-contrast axial T1 sections. The gray level intensity, standard deviation of histogram, entropy, uniformity, skewness, and kurtosis values were determined by texture analysis.Results: Comparison of the pre- and post-radiotherapy values showed an increase in entropy (6.97±0.37 vs. 7.20±0.30, p = 0.014) and a decrease in uniformity (0.21±0.12 vs.0.16±0.08, p = 0.049). Therefore, radiation therapy was determined to have caused increased heterogeneity in the active tumor region of glioblastoma. The median follow-up was 7.5 [95% confidence interval (1.8-21.63)] months, while the median overall survival was 12.5 [95% confidence interval (4.24-20.81)] months. Young age, high performance statusand low entropy value after radiotherapywere associated with longer survival according to the Kaplan-Meier analysis (p = 0.014, p = 0.031, p = 0.034, respectively).Conclusion: Based on these results,entropy measurements can be recommended for use as a new prognostic factor for glioblastoma.Keywords: Glioblastoma; Entropy; Radiotherapy; Survival; Texture Analysis.